Ore Pretreatment Methods for Grinding: Journey and Prospects. (2nd January 2019) - Singh, Veerendra; Dixit, Prashant; Venugopal, R; Venkatesh, K Bhanu
ABSTRACT: Pretreatment of ores to improve energy efficacy of grinding has been explored for decades. However, many of these techniques are still at developmental stages and a review has been presented in this paper to discuss the research journey and problems associated with commercialization of these techniques. This review reveals that a variety of stress-generating techniques have been used to treat the composition and morphology of particles to improve the grinding process. Grinding additives are used commercially successful technology while microwave pretreatment also has been successfully piloted. Newly developed techniques such as ultrasonics and electric disintegration have shown potential for success but the cost economics of these processes is still not as attractive as desired. Incipient techniques based on bio-milling, shock waves, and nuclear hold promise for the future. It is also expected that the technological advances around information technology, instrumentation, and energy science will help to solve techno-economic challenges associated with commercialization of the known technologies. Demand for energy-efficient grinding pretreatment methods will grow in the future considering the depletion of high-grade resources and stringent environmental constraints related to reject disposal.